Estimation of immunity of the winter grain varieties sown in the south of Russia to the pink snow mold pathogen (Microdochium nivale) - G. V. Volkova; Ya. V. Yakhnik; O. V. Tarancheva (Зерновое хозяйство России, 2021)
The purpose of the current study was to estimate immunity of the winter grain varieties sown in the south of Russia to the pink snow mold pathogen (Microdochium nivale (Fr.) Samuels & I.C. Hallett) in the sprouting phase. For resistance to M. nivale there have been studied 35 winter wheat varieties sown in the south of the Russian Federation, 19 winter barley varieties and 4 variety samples and 13 winter triticale varieties developed in the LLC “Agrostandart”, FSBSI RCG named after P.P. Lukyanenko, FSBSI FRC Kabardino-Balkarian Research Center of the RAS, FSBSI “ARC Donskoy”, FSBSI “North Caucasian FRSC”, FSBSI “FRAC”, NPO “KUBANZERNO”, FSBEI HE “KubSAU”. There has been substantiated a methodological approach to conducting research on immunological estimation of winter grain varieties in the laboratory conditions. The optimal temperature for the cultivation of the pathogen was +10/+15 °C (with a photoperiod of 12 hours). There was found that the required temperature to stimulate sporulation was +5 °C. The optimum temperature for the incubation period was +5 °C at 85% humidity. There has been established that the only winter wheat variety ‘Dolya’ had a very high resistance degree to pink snow mold; the varieties ‘Antonina’ and ‘Brigada’ had a high resistance degree; 21 varieties were classified as resistant. M. nivale resistance was demonstrated by 9 winter barley varieties and 3 variety samples (‘Versal’, ‘Iosif’, ‘KA-12’, ‘KA-5/KA-3’, ‘KA-5/KA-1’, ‘Karrera’, ‘Kondrat’, ‘Kubagro-1’, ‘Lazar’, ‘Master’, ‘Romans’, ‘Sarmat’). Among the studied winter triticale varieties, 4 varieties had a very high resistance degree (‘Argus’, ‘Slon’, ‘Tikhon’, ‘Ullubiy’) and 9 varieties had a high resistance degree to pink snow mold pathogen (‘Aznavur’, ‘Argo’, ‘Arioso’, ‘Valentin 90’, ‘Iliya’, ‘Sotnik’,’ Styuard’, ‘Forte’, ‘Khleborob’).